Mining Affymetrix microarray data for long non-coding RNAs: altered expression in the nucleus accumbens of heroin abusers - Michelhaugh, Sharon K; Lipovich, Leonard; Blythe, Jason; Jia, Hui; Kapatos, Gregory; Bannon, Michael J (Journal of neurochemistry, 2011)
J. Neurochem. (2011) 116, 459-466. ABSTRACT: Although recent data suggest that some long non-coding RNAs (lncRNAs) exert widespread effects on gene expression and organelle formation, lncRNAs as a group constitute a sizable but poorly characterized fraction of the human transcriptome. We investigated whether some human lncRNA sequences were fortuitously represented on commonly used microarrays, then used this annotation to assess lncRNA expression in human brain. A computational and annotation pipeline was developed to identify lncRNA transcripts represented on Affymetrix U133 arrays. A previously published dataset derived from human nucleus accumbens was then examined for potential lncRNA expression. Twenty-three lncRNAs were determined to be represented on U133 arrays. Of these, dataset analysis revealed that five lncRNAs were consistently detected in samples of human nucleus accumbens. Strikingly, the abundance of these lncRNAs was up-regulated in human heroin abusers compared to matched drug-free control subjects, a finding confirmed by quantitative PCR. This study presents a paradigm for examining existing Affymetrix datasets for the detection and potential regulation of lncRNA expression, including changes associated with human disease. The finding that all detected lncRNAs were up-regulated in heroin abusers is consonant with the proposed role of lncRNAs as mediators of widespread changes in gene expression as occur in drug abuse.